2015
DOI: 10.1038/aps.2015.16
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of PEGylated recombinant human endostatin (M2ES) in rats

Abstract: Aim: M 2 ES is PEGylated recombinant human endostatin. In this study we investigated the pharmacokinetics, tissue distribution, and excretion of M 2 ES in rats. Methods: 125 I-radiolabeled M 2 ES was administered to rats by intravenous bolus injection at 3 mg/kg. The pharmacokinetics, tissue distribution and excretion of M 2 ES were investigated using the trichloroacetic acid (TCA) precipitation method. Results: The serum M 2 ES concentration-time curve after a single intravenous dose of 3 mg/kg in rats was fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…We next screened the EOMA‐secreted pro‐angiogenic factor(s) that is specifically disrupted by thalidomide. As reported , EOMA secretes angiogenesis factors including ADAMTS1, angiogenin, Cyr61, endostatin, endothelin‐1, HB‐EGF, CXCL1, PDGF‐AA, PDGF‐AB, PlGF‐2, SDF‐1, Serpin E1, and TIMP‐1. We therefore examine whether thalidomide can repress the transcription of the aforementioned factors by qRT‐PCR.…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…We next screened the EOMA‐secreted pro‐angiogenic factor(s) that is specifically disrupted by thalidomide. As reported , EOMA secretes angiogenesis factors including ADAMTS1, angiogenin, Cyr61, endostatin, endothelin‐1, HB‐EGF, CXCL1, PDGF‐AA, PDGF‐AB, PlGF‐2, SDF‐1, Serpin E1, and TIMP‐1. We therefore examine whether thalidomide can repress the transcription of the aforementioned factors by qRT‐PCR.…”
Section: Resultsmentioning
confidence: 63%
“…To examine whether thalidomide can also inhibit hemangioendothelioma, we first performed in vivo study by utilizing mouse EOMA, which exhibits endothelial cell properties. EOMA cells were subcutaneously injected into in nude mice and formed tumors after 7 days as reported [17,18]. As shown in Figure 1a-c, hemangioendothelioma growth was inhibited by thalidomide administration.…”
Section: R E S U L T Smentioning
confidence: 72%
See 1 more Smart Citation
“…Since the intrinsic labeling does not alter the structure of the molecule and possesses fast identical physicochemical property to analytes, it can represent the pharmacokinetic behavior of the analytes precisely. Radiolabeling is commonly used in the studies of the in vivo absorption, distribution, metabolism, and excretion (ADME) processes of PEG [62,78,79], PEGylated small molecules [80], PEGylated peptides [81–83], PEGylated proteins [84–86], and PEGylated nanoparticles [10,87–93], which will be discussed in the following parts respectively.…”
Section: Bioanalytical Methods For Polyethylene Glycols and Pegylatedmentioning
confidence: 99%
“…To prolong the circulating half‐life of endostatin and reduce its dosing frequency, PEG was applied to produce an N‐terminal mono‐PEGylated recombinant human endostatin . Li et al reported that PEG modification substantially prolongs the circulation time of MES; the half‐life of MES (3 mg/kg) and M 2 ES (3 mg/kg) were 3.9 and 60.1 hours, respectively. In addition, M 2 ES can significantly reduce dosing frequency compared with other similar products in the market .…”
Section: Introductionmentioning
confidence: 99%